Assessment of Black Carbon Concentration in Rice Straw Open Burning Season in Lai Yen Commune, Hanoi Suburban Area - Hoang, Xuan Co (ĐHQGHN, 2017)
In recent years, rice straw open burning (RSOB) activity has commonly occurred after the harvest in the countryside of Hanoi. This activity has caused negative impacts on air quality, especially it emits a large amount of black carbon (BC), a short lived climate pollutant (SLCP). As the other SLCPs, BC directly affects human health and ecosystem. This paper presents the results of measured BC concentrations in RSOB season in Lai Yen commune, Hoai Duc district in Hanoi. The results showed that the hourly average BC concentrations in three monitoring periods were 8.43 ± 0.67 µg/m3 (23 - 25 Oct. 2015), 7.64 ± 0.73 µg/m3 (26 - 28 Feb. 2016) and 3.74 ± 0.30 µg/m3 (15 - 19 Jun. 2016), respectively. The lowest BC concentration was 0.36µg/m3 while the highest nearly reached 36.8µg/m3. BC concentration in this study is higher than that of Lang air quality-monitoring station. This result is useful for national policy makers and managers for tighter control of RSOB activities.